Evaluación de teta de vaca (Solanum mammosum L) en el control de (Rhipicephalus microplus) en bovinos - Ocampo Zambrano, Victor Manuel (2023)
The present study was developed to evaluate the effect of cow teat (Solanum Mammosum L) in the in vitro and in vivo control of ticks (Rhipicephalus microplus). Four treatments were determined: (T0) commercial garrapaticide (Amitraz) 1 ml, (T1): aqueous extract of cow teat (Solanum Mammosum L) at 13%, (T2): aqueous extract at 20%, and (T3): The variability was established by means of a completely randomized experimental design (DCA) with statistical inferences of homoscedasticity of data (Shapiro Wilk), analysis of variance (Anova) and Tukey significance test at 5%, which were able to verify the behavior of the variables of tick mortality and oviposition inhibition. The results report that (T3) shows the best oviposition inhibition parameters with 27% and the best efficacy indexes in tick mortality at 24 hours (66%), 48 hours (74%) and 72 hours (83%), values contrasted with the control treatment (T0) which presented an efficacy index of 100% in in vitro and in vivo tests on the estimated variables. It is concluded that cow teat has an ixodicidal effect on ticks using 27% concentration.